Impact of dividend policy on firm performance: evidence from Sri Lankan listed companies - Tharsika, K.; Thaneshan, G. (Sabaragamuwa University of Sri Lanka, 2023)
One of the most controversial issues in the field of finance is the behavior of the dividend policy, which is still given considerable attention in developing economies. There are limited research studies investigating the associations between dividend policies and financial performance, particularly in developing nations. Thus, the purpose of this paper is to investigate the impact of dividend policy on the firm performance of Sri Lankan publicly listed companies. The population of interest for this study consists of 289 companies registered on the Colombo Stock Exchange, and 100 companies were selected at random. The dependent variable is firm performance, which is measured by return on assets and return on equity, and the independent variable is dividend policy, which is measured by dividend payout ratio and dividend yield. The data are collected from the annual reports of selected companies for the period from 2017 to 2022, which are available on the Colombo Stock Exchange and the company website. The results of Hausman's model specification test concluded that the fixed effects model is most appropriate for testing the formulated hypothesis. The regression outcomes indicate a positive relationship between dividend policy and firm performance, but dividend yield has an insignificant impact on return on assets. The conclusion of the study is that dividend policy explains a significant portion of a company's performance, indicating that dividend policy has a statistically significant effect on a company's performance. The results of this research will assist decision-makers, prospective investors, academics, econometricians, and other interested parties in making decisions regarding the managerial implications of the economy and corporate sector.
Keywords: Dividend policy; Firm performance; Hausman's model specification test